20-Year Climatology of NO3 − and NH4 + Wet Deposition at Ny-Ålesund, Svalbard - Rafael Kühnel; Tjarda J. Roberts; Mats P. Björkman; Elisabeth Isaksson; Wenche Aas; Kim Holmén; Johan Ström (Advances in Meteorology)
A 20-year dataset of weekly precipitation observations in Ny-Ålesund, Svalbard, was analysed to assess atmospheric wet deposition of nitrogen. Mean annual total nitrogen deposition was 74 mg N/(m2 yr) but exhibited large interannual variability and was dominated by highly episodic “strong” events, probably caused by rapid transport from European sources. The majority (90%) of precipitation samples were defined as “weak” (<2 mg N/m2) and contributed an annual baseline of ~17 mg N/(m2 yr), whereas 10% of precipitation samples were defined as “strong” (>2 mg N/m2) and additionally contributed up to 225 mg N/(m2 yr). Nitrate deposition largely occurred in samples within the solid-precipitation season (16 September–2 June), and ammonium deposition occurred equally in both solid and liquid seasons. Trends of reactive nitrogen emissions from Europe are uncertain, and increasing cyclonic activity over the North Atlantic caused by a changing climate might lead to more strong deposition events in Svalbard.